Frustration tolerance and resilience in university students in Lima, Peru, 2023 - Cervantes Chávez, Laura Karina (2024)
Objective: To determine the relationship between frustration tolerance and resilience in university students in Lima, Peru. Methods: A quantitative approach with a simple correlational and cross-sectional design was applied. The sample consisted of 316 university students, who were administered the Frustration Tolerance Scale (FTS) and the Resilience Scale (RS). A set of statistical analyses was employed to examine the relationship between resilience (R) and frustration tolerance (FT) in university students, as well as the variations of these variables according to demographic and academic characteristics. Spearman's r test was used for inferential analysis, with a rho = 0.65, and the statistical signifcance value was p < 0.01. Results: Resilience, measured as a single dimension, had a mean of 5.46 (SD = 0.81), with values ranging from 2.68 to 7. Regarding frustration tolerance, which was evaluated in dimensions, the following means were reported: in the personal dimension, the mean was 2.24 (SD = 0.36); in the work dimension, the mean was 2.20 (SD = 0.30); in the social dimension, 2.22 (SD = 0.30); and in the family dimension, 2.33 (SD = 0.37). Conclusions: There are significant correlations between resilience and frustration tolerance, both in general terms and in the specific personal and work dimensions.